Sensitive, simple and fast voltammetric determination of pesticides in juice samples by novel BODIPY-phthalocyanine-SWCNT hybrid platform - Köksoy, Baybars; Akyuz, Duygu; Senocak, Ahmet; Durmus, Mahmut; Demirbas, Erhan (Pergamon-Elsevier Science Ltd, 2021)
The present work describes the first synthesis of novel asymmetric zinc (II) phthalocyanine (ZnPc) including three boron dipyrromethene (BODIPY) and one ethyloxy azido moieties. Moreover, single walled carbon nanotube (SWCNT) surface was functionalized by this ZnPc containing BODIPY; using the azide-alkyne Huisgen cycloaddition (Click) reaction to obtain SWCNT-ZnPc hybrid material. Structural, thermal and morphological characterizations of both ZnPc and SWCNT-ZnPc hybrid were carried out in-depth by spectroscopic, thermal and microscopic techniques. In this study, the synthesized SWCNT-ZnPc material was decorated on composite glassy carbon electrode (GCE) by means of an easy and a practical drop cast method. The modified electrode was tested as a non-enzymatic electrochemical sensor in various common pesticides such as methyl parathion, deltamethrin, chlorpyrifos and spinosad. Electrochemical behavior of non-enzymatic electrode (GCE/SWCNT-ZnPc) was determined via cyclic voltammetry and differential pulse voltammetry. The non-enzymatic sensor demonstrated high selectivity for methyl parathion in a wide linear range (2.45 nM-4.0 x 10(-8) M), low limit of detection value (1.49 nM) and high sensitivity (0.1847 mu A nM(-1)). Also, the developing non-enzymatic sensor exhibited good repeatability (RSD = 2.3% for 10 electrodes) and stability (85.30% for 30 days). Validation guidelines by HPLC and statistical analysis showed that the proposed voltammetric method were precise, accurate, sensitive, and can be used for the routine quality control of methyl parathion determination in juice samples.
Keywords: BODIPY; Phthalocyanine; SWCNT; Non-enzymatic; Pesticide sensor; Electrochemical sensor